Ð§ÑƒÐ²ÑÑ‚Ð²Ð¸Ñ‚ÐµÐ»ÑŒÐ½Ð¾ÑÑ‚ÑŒ ÑÑ€Ð¸Ñ‚Ñ€Ð¾Ñ†Ð¸Ñ‚Ð¾Ð² Ð¼Ð»ÐµÐºÐ¾Ð¿Ð¸Ñ‚Ð°ÑŽÑ‰Ð¸Ñ… Ðº Ð¸Ð·Ð¼ÐµÐ½ÐµÐ½Ð¸ÑŽ Ñ‚ÐµÐ¼Ð¿ÐµÑ€Ð°Ñ‚ÑƒÑ€Ð½Ñ‹Ñ… Ð¸ Ð¾ÑÐ¼Ð¾Ñ‚Ð¸Ñ‡ÐµÑÐºÐ¸Ñ… ÑƒÑÐ»Ð¾Ð²Ð¸Ð¹ ÑÑ€ÐµÐ´Ñ‹ - Ershov, S. S.; Orlova, N. V.; Shpakova, N. M. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2004)
The authors have investigated the peculiarities of osmotic and temperature mammalian erythrocyte sensitivity (bovine, canine and equine) and chlorpromazine (ChP) effect on their hypertonic hemolysis. The obtained results have allowed to reveal the species’ erythrocytes sensitivity to various stress factors. The minimum sensitivity of canine cells is shown and the maximum of bovine erythrocytes both to an increase of NaCl concentration in isothermal conditions and to the change in temperature of hypertonic incubation medium as well. ChP adding to hypertonic medium allows decreasing in the damage level of mammalian erythrocytes. Antihemolytic activity values of the presented compound for all the investigated erythrocytes do not differ considerably (about 80%), meanwhile the range of ChP effective concentrations increases in the row: bovine, equine, canine.